Glyceryl Trinitrate for Acute Intracerebral Hemorrhage: Results From the Efficacy of Nitric Oxide in Stroke (ENOS) Trial, a Subgroup Analysis. Issue 1 (January 2016) - Krishnan, Kailash; Scutt, Polly; Woodhouse, Lisa; Adami, Alessandro; Becker, Jennifer L.; Berge, Eivind; Cala, Lesley A.; Casado, Ana M.; Caso, Valeria; Chen, Christopher; Christensen, Hanna; Collins, Ronan; et al.
Abstract : Background and Purpose—: The Efficacy of Nitric Oxide in Stroke (ENOS) trial found that transdermal glyceryl trinitrate (GTN, a nitric oxide donor) lowered blood pressure but did not improve functional outcome in patients with acute stroke. However, GTN was associated with improved outcome if patients were randomized within 6 hours of stroke onset. Methods—: In this prespecified subgroup analysis, the effect of GTN (5 mg/d for 7 days) versus no GTN was studied in 629 patients with intracerebral hemorrhage presenting within 48 hours and with systolic blood pressure ≥140 mm Hg. The primary outcome was the modified Rankin Scale at 90 days. Results—: Mean blood pressure at baseline was 172/93 mm Hg and significantly lower (difference −7.5/−4.2 mm Hg; both P ⩽0.05) on day 1 in 310 patients allocated to GTN when compared with 319 randomized to no GTN. No difference in the modified Rankin Scale was observed between those receiving GTN versus no GTN (adjusted odds ratio for worse outcome with GTN, 1.04; 95% confidence interval, 0.78–1.37; P =0.84). In the subgroup of 61 patients randomized within 6 hours, GTN improved functional outcome with a shift in the modified Rankin Scale (odds ratio, 0.22; 95% confidence interval, 0.07–0.69; P =0.001). There was no significant difference in the rates of serious adverse events between GTN and no GTN. Conclusions—: In patients with intracerebral hemorrhage within 48 hours of onset, GTN lowered blood pressure was safe but did not improve functional outcome. Very early treatment might be beneficial but needs assessment in further studies. Clinical Trial Registration—: URL:http://www.isrctn.com/ISRCTN99414122 . Unique identifier: 99414122. Abstract : Supplemental Digital Content is available in the text.